Are Ghana’s Public-Sector employees overpaid? Understanding the public/private wage gap and its effect on the government deficit - Younger, Stephen D.; Osei-Assibey, Eric (International Food Policy Research Institute, 2017)
Ghana is again experiencing large and chronic fiscal deficits that many analysts attribute to a sharp increase in its the public-sector wage bill. This study uses macroeconomic and household survey data to examine public employment and public wages both historically and in comparison with private-sector wages. Although we do find a public-sector wage premium in the most recent data (for 2012/2013), it is not as large as one would expect from the macro data, totaling only 15 to 28 percent of the public-sector wage bill, or 2 to 3 percent of gross domestic product. That is far from enough to eliminate the government deficit. To make further reductions in the wage bill, policymakers must either make the normative case that public-sector workers should be paid less than private-sector workers with similar qualifications, something that will be difficult politically, or they must adjust the required skill levels of public-sector employees downward, something that may not make administrative sense. There is some low-hanging fruit in the public-sector wage bill, but not enough to resolve Ghana’s fiscal crisis.